MENGENALKAN KONSEP SAINS PERMULAAN DENGAN EKSPLORASI LINGKUNGAN SEKITAR - Ilzam Dhaifi; Husniati Husniati; Muslihan Muslihan (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2022)
Learning science through exploration of the surrounding environment is beneficial for children because it can create a pleasant atmosphere as well as create imagination in children which in turn can increase children's knowledge naturally. The research objective is to describe the process and results of increasing scientific knowledge through the method of exploring the surrounding environment. The type of research used is Classroom Action Research (CAR) which is carried out in stages from pre-cycle, cycle I to cycle II. Each cycle consists of Planning, Action, Observation, and Reflection. The results of this study include: (1) the process of exploring the surrounding environment is carried out by the teacher inviting children to explore the surrounding nature; observing, identifying, planting and caring for plants (2) The results showed an increase in children's science knowledge through environmental exploration, where children were able to work and were able to be patient waiting for their turn, namely pre-cycle, the percentage value reached 41.17%, while the average achievement indicator of children is 4.05. After the first cycle of action, the percentage value reached 58.82%, while the average achievement of the child indicators was 5.29. and the second cycle of action, the percentage value reached 88.23%. the average score of the child's achievement indicator is 7.17. It has been found that a comparison of the level of children's science knowledge shows that children experience development in their scientific knowledge.